Performance of active nickel loaded lignite char catalyst on conversion of coffee residue into rich-synthesis gas by gasification - Suparin Chaiklangmuang (2018)
© 2017 Energy Institute Performance of nickel-loaded lignite char catalyst on conversion of coffee residue into synthesis gas by catalytic steam gasification was carried out at low reaction temperatures ranging from 500 °C to 650 °C in the two-stage quartz fixed bed reactor. The effects of steam pressures (30, 36 and 50 kPa corresponding to S/B = 2.23, 2.92 5.16, respectively) and catalyst to biomass ratios (C/B ratio = 0, 1, 3) were considered. Nickel-loaded lignite char was prepared as a catalyst with a low nickel loading amount of 12.9 wt%. The gas yields in the catalytic steam gasification process strongly depended on the reaction temperature and C/B ratio. The total gas yields obtained in catalytic steam gasification was higher than that of catalytic pyrolysis, steam gasification and non-catalytic pyrolysis with steam absence by factors of 3.0, 3.8 and 7.7, respectively. To produce the high synthesis gas, it could be taken at 600 °C with total gas yields of 67.13 and 127.18 mmol/g biomass-d.a.f. for C/B ratios of 1.0 and 3.0, respectively. However, the maximum H2/CO ratio was 3.57 at a reaction temperature of 600 °C, S/B of 2.23 and C/B of 1.0. Considering the conversion of coffee residue by catalytic steam gasification using the nickel-loaded lignite char catalyst, it is possible to covert the coffee residue volatiles into rich synthesis gas.